IMF Managing Director's Statement to the Development Committee, April 2020. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2020)
The global coronavirus outbreak is a crisis like no other and poses daunting challenges for policymakers in many emerging market and developing economies (EMDEs), especially where the pandemic encounters weak public health systems, capacity constraints, and limited policy space to mitigate the outbreak's repercussions. A severe economic impact in the first half of 2020 is inevitable. Medium-term projections are clouded by uncertainty regarding the pandemic's magnitude and speed of propagation, as well as the longer-term impact of measures to contain the outbreak, such as travel bans and social distancing. However, most EMDEs are already suffering from disruptions to global value chains, lower foreign direct investment, capital outflows, tighter financing conditions, lower tourism and remittances receipts, and price pressures for some critical imports such as foods and medicines. Commodity exporters have to absorb, in addition, a sharp decline in export prices, notably for oil. Further, in most countries, the coronavirus outbreak is producing unanticipated health spending needs and revenue losses as activity slows. Coping with these challenges is especially difficult for countries with limited administrative capacity, tight external financing constraints and/or already high debt levels, and thus requires substantial support from the international community.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: China, People's Republic of